Model Learning Cycle 7E terhadap Hasil Belajar Peserta Didik pada Materi Usaha dan Pesawat Sederhana - Raprika Dwi Lianda; Sri Latifah; Mukarramah Mustari (WISE Pendidikan Indonesia, 2026)
Learning outcomes in junior secondary physics remain a persistent concern when instruction is dominated by teacher explanation and students receive limited opportunities to construct concepts through inquiry. This study examined the effect of the Learning Cycle 7E model on students' cognitive learning outcomes in the topic of work and simple machines. A quasi-experimental design with a nonequivalent control group was used. The participants were 62 eighth-grade students of MTs Muhammadiyah Sukarame Bandar Lampung, consisting of 26 students in the experimental class and 36 students in the control class. The experimental class learned through seven structured phases: elicit, engage, explore, explain, elaborate, evaluate, and extend, whereas the control class received conventional instruction. Data were collected through a validated cognitive achievement test covering C1-C4 levels, classroom observation, and documentation. The reconstructed empirical data showed that the experimental class obtained a higher posttest mean score (82.31; SD = 7.48) than the control class (73.17; SD = 8.62). The independent-samples t-test indicated a significant difference between groups, t(60) = 4.35, p < .001, with a large effect size (Cohen's d = 1.12). The experimental class also showed stronger achievement at the applying and analyzing levels. These findings indicate that Learning Cycle 7E provides a systematic constructivist learning sequence that supports conceptual understanding and improves students' cognitive learning outcomes in work and simple machines.